Kebijakan Hukum Pidana dalam Penanggulangan Kejahatan di Dunia Perbankan - Muchtar, Henni (Jurnal Demokrasi, 2010)
Indonesia is rich with many cases and big scandals that connected to white collar crime, even that occurred in capital market, at a bank, or the other sector. One of big cases, which cause contraversion in perception of Indonesian People, is presumption of accounting manipulation report from Lippo Bank Direction. The proof cause Bapepam imposes a fine in the amount for 2.5 billion rupiahs to Lippo Bank Direction. However, it is not a simply case because it is still have another law implication from imposition of fine so that it is important to make criminal policy to solve Lippo Bank Scandal. Kata Kunci: White collar crime, Lippo Bank Scandal. Criminal Policy